Balanced forced‐diuresis as a renal protective approach in cardiac surgery: Secondary outcomes of electrolyte changes. Issue 11 (19th August 2021) - Luckraz, Heyman; Giri, Ramesh; Wrigley, Benjamin; Nagarajan, Kumaresan; Senanayake, Eshan; Sharman, Emma; Beare, Lawrence; Nevill, Alan
Abstract: Objectives: Forced‐diuresis during cardiopulmonary bypass (CPB) can be associated with significant electrolyte shifts. This study reports on the serum electrolyte changes during balanced forced‐diuresis with the RenalGuard® system (RG) during CPB. Methods: Patients at risk of acute kidney injury (AKI)—(history of diabetes &/or anaemia, e‐GFR 20–60 ml/min/1.73 m 2, anticipated CPB time >120 min, Log EuroScore >5)—were randomized to either RG (study group) or managed as per current practice (control group). Results: The use of RG reduced AKI rate (10% for RG and 20.9% in control, p = .03). Mean urine output was significantly higher in the RG group during surgery (2366 ± 877 ml vs. 765 ± 549 ml, p < .001). The serum potassium levels were maintained between 3.96 and 4.97 mmol/L for the RG group and 4.02 and 5.23 mmol/L for the controls. Median potassium supplemental dose was 60 (0–220) mmol (RG group) as compared to 30 (0–190) mmol for control group over first 24 h ( p < .001). On Day 1 post‐op, there were no significant differences in the serum sodium, potassium, calcium, magnesium, phosphate, and chloride levels between the two groups. Otherwise, postoperative clinical recovery was also similar. Conclusions: Balanced forced‐diuresis with the RG reduced AKI rates after on‐pump cardiac surgery compared to controls. Although the RG group required higher doses of IV potassium replacement in the postoperative period, normal serum levels of potassium were maintained by appropriate intravenous potassium supplementation and the clinical outcomes between groups were similar.